PENINGKATAN HASIL BELAJAR PPKN PADA KURIKULUM MERDEKA MATERI MEMBANGUN JATI DIRI DALAM KEBINEKAAN MENGGUNAKAN MEDIA AUDIO-VISUAL UNTUK SISWA KELAS IV SDN 2 SADANG: penelitian tindakan kelas - Muftia Salsabilla; Erik Aditia Ismaya; Wawan Shokib Rondli (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study uses the student team achievement (STAD) model and audio-visual media to increase Civics learning in Merdeka Class IV at SDN 2 Sadang. This research uses the student team achievement (STAD) model and audio-visual medium to improve civics learning in unit 3 "Building Identity in Diversity" in fourth graders at SDN 2 Sadang. Class Action Research was conducted in SDN 2 Sadang class IV with 20 students. The research took place during II Cycle, which includes planning, implementing, observing, and reflecting. The independent variables are STAD and Audio Visual Media. Related variable is Learning Outcomes. This study collected data through interviews, observation, testing, and documentation. Quantitative and qualitative data are analysed. The knowledge learning results of pupils rose from cycle I (55% to cycle II 80%). Cycle II teacher abilities grew 83% from cycle I (71%). Student learning activities increased from cycle I (68%) to cycle II (82%). Based on research in class IV at SDN 2 Sadang, civics learning outcomes in the autonomous curriculum on creating identity in diversity utilising audio-visual media for fourth graders have increased. Researchers recommend